A comment on continuous spin representations of the Poincaré group and perturbative string theory. Issue 11 (16th October 2014) - Font, A.; Quevedo, F.; Theisen, S.
Abstract We make a simple observation that the massless continuous spin representations of the Poincaré group are not present in perturbative string theory constructions. This represents one of the very few model‐independent low‐energy consequences of these models.